2017
DOI: 10.1111/echo.13648
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial phasic function and heart rate variability in patients with systemic sclerosis: A new part of the old puzzle

Abstract: Left atrial (LA) phasic function, assessed by both volumetric and strain method, as well as cardiac autonomic nervous function is significantly deteriorated in SSc patients. Skin score and HRV indices correlate with LA phasic function parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
3
2
Order By: Relevance
“…Tigen et al 27 have reported that LA reservoir and conduit functions were similar between the groups, but other studies have reported one or more decreased LA mechanics indexes. [28][29][30][31] The present meta-analysis showed that εR and εCD were decreased, whereas no significant differences were found for εCT. For RA, εR was also confirmed to be decreased.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Tigen et al 27 have reported that LA reservoir and conduit functions were similar between the groups, but other studies have reported one or more decreased LA mechanics indexes. [28][29][30][31] The present meta-analysis showed that εR and εCD were decreased, whereas no significant differences were found for εCT. For RA, εR was also confirmed to be decreased.…”
Section: Discussioncontrasting
confidence: 61%
“…Speckle tracking index for evaluation of atrium mechanics includes εR, εCD and εCT. Tigen et al 27 have reported that LA reservoir and conduit functions were similar between the groups, but other studies have reported one or more decreased LA mechanics indexes 28–31. The present meta-analysis showed that εR and εCD were decreased, whereas no significant differences were found for εCT.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…However, a recent meta-analysis revealed that SSc patients have a lower strain than healthy controls for the majority of STE parameters, supporting the presence of impaired myocardium involving both ventricles and atriums [46 ]. Tigen et al [47] reported that left atrial (LA) reservoir and conduit function was similar between the groups, but other studies have reported one or more decreased LA mechanics indices [48][49][50][51]. Although only two studies [51,52] were included in the evaluation of right atrium conduit (eCD), they both showed impaired right atrial (RA) mechanics with decreased eCD.…”
Section: Echocardiography: the Traditional Diagnostic Frontlinementioning
confidence: 99%
“…Although SSc is a multisystemic condition, cardiopulmonary manifestations are responsible for up to 85% of mortality [ 2 ]. In the heart, all structures can be affected by SSc, leading to inflammation, oxidative stress, vascular damage, and fibrosis [ 3 ]. The main underlying mechanism seems to be impairment of the microcirculation, with abnormal vasoreactivity due to dysfunction of the autonomic nervous system (ANS) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%